CORRELATION OF CLINICAL LABORATORY PARAMETERS AND DEMOGRAPHY WITH PHARMACOKINETICS OF TACROLIMUS – A NARROW THERAPEUTIC INDEX DRUG - SAJAD KHALIQ DAR; ARSHAD H KHUROO; MOHD AKHTAR; SUDERSHAN KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: During clinical pharmacokinetic (PK) studies, human volunteers are subjected to screening with respect to clinical pathology parameters, based on which volunteers are considered healthy or not healthy. Even for the screened healthy volunteers, these parameters vary from person to person, and the reason is obvious, these parameters fall in a well-defined acceptable range. The diversity in the physiological and pathological values, even within the acceptable limits, could be significant enough to have an impact on systemic drug exposure. The present research was aimed to study the correlation between the clinical parameters (used for screening) and PKs of tacrolimus, which is a narrow therapeutic index (NTI) drug. Methods: Twenty-four healthy adult human subjects, aged between 18 and 50 years, were recruited in this single-dose, open-label, balanced, randomized crossover study under fasting conditions. The eligibility of volunteers was based on inclusion and exclusion criteria mentioned in the study protocol, and screened healthy volunteers were enrolled in the study. Dose administration was done after fasting of 10 h and blood samples were collected for measurement of the tacrolimus concentrations by a validated liquid chromatography-mass spectrometry method. PK parameters were calculated followed by their correlation analysis with respective clinical pathological/screening parameters. Results: The results of this study suggest that values of clinical parameters can increase or decrease the systemic exposure of the tacrolimus. A significant correlation was observed between PK estimates and age, serum creatinine levels, hematology, and total bilirubin. The coefficient of correlation was approximately 0.9. Conclusion: The information on the correlation of demography, hematology, serology, and biochemistry with PK would assist PK researchers in having an optimum study design for the successful conduct of clinical studies, especially for NTI, cytotoxic, or drug molecules with high PK variability. These studies will also support clinicians to devise an effective drug therapy, especially for NTI medications intended for long-term treatment.